Child Care and Human Development: Insights from Jewish History in Central and Eastern Europe, 1500–1930*. Issue 623 (29th May 2019) - Botticini, Maristella; Eckstein, Zvi; Vaturi, Anat
Abstract: Economists increasingly highlight the role that human capital formation, institutions and cultural transmission may play in shaping health, knowledge and wealth. We study one of the most remarkable instances in which religious norms and childcare practices had a major impact: the history of the Jews in central and eastern Europe from 1500 to 1930. We show that while birth rates were about the same, infant and child mortality among Jews was much lower and accounted for the main difference in Jewish versus non-Jewish natural population growth. Jewish families routinely adopted childcare practices that recent medical research has shown as enhancing children's well-being.